The Role of Competence and Organizational Culture in Determining Organizational Commitment and Its Effect on Employee Performance Bali Provincial Department of Industry and Trade - Ayu Asih Eriani, Anak Agung; Widnyana, I Wayan; Sujana, I Wayan (International Journal of Scientific Research and Management (IJSRM), 2023)
Employees are the main asset of the organization and have a strategic role in the organization, namely as thinkers, planners and controllers of organizational activities. An organization that has a strong culture will basically improve employee performance, foster a spirit of togetherness among its members, increase a sense of comfort and loyalty to the organization and be able to improve organizational performance. This study aims to test and explain research problems related to the role of competence and organizational culture in determining organizational commitment and its effect on employee performance. This research was conducted at the Bali Provincial Industry and Trade Office with a population of 84 by applying sampling techniques with saturated samples. The findings of this study are that competence and organizational culture have a positive and significant effect on organizational commitment. Likewise with the organization's commitment to employee performance. So it can be concluded that organizational competence and culture are able to increase organizational commitment so that employee performance will also increase. With these results, it is hoped that therganization can increase opportunities, facilities, training and budgets to improve employee competence which will affect the performance of employees in the Bali Provincial Industry and Trade Office.